Cerebrospinal fluid lysosomal enzymes and alpha‐synuclein in Parkinson's disease. Issue 8 (16th January 2014) - Parnetti, Lucilla; Chiasserini, Davide; Persichetti, Emanuele; Eusebi, Paolo; Varghese, Shiji; Qureshi, Mohammad M.; Dardis, Andrea; Deganuto, Marta; De Carlo, Claudia; Castrioto, Anna; Balducci, Chiara; Paciotti, Silvia; et al.
ABSTRACT To assess the discriminating power of multiple cerebrospinal fluid (CSF) biomarkers for Parkinson's disease (PD), we measured several proteins playing an important role in the disease pathogenesis. The activities of β‐glucocerebrosidase and other lysosomal enzymes, together with total and oligomeric α‐synuclein, and total and phosphorylated tau, were thus assessed in CSF of 71 PD patients and compared to 45 neurological controls. Activities of β‐glucocerebrosidase, β‐mannosidase, β‐hexosaminidase, and β‐galactosidase were measured with established enzymatic assays, while α‐synuclein and tau biomarkers were evaluated with immunoassays. A subset of PD patients (n = 44) was also screened for mutations in the β‐glucocerebrosidase‐encoding gene (GBA1). In the PD group, β‐glucocerebrosidase activity was reduced (P < 0.05) and patients at earlier stages showed lower enzymatic activity (P < 0.05); conversely, β‐hexosaminidase activity was significantly increased (P < 0.05). Eight PD patients (18%) presented GBA1 sequence variations; 3 of them were heterozygous for the N370S mutation. Levels of total α‐synuclein were significantly reduced (P < 0.05) in PD, in contrast to increased levels of α‐synuclein oligomers, with a higher oligomeric/total α‐synuclein ratio in PD patients when compared with controls (P < 0.001). A combination of β‐glucocerebrosidase activity, oligomeric/total α‐synuclein ratio, and age gave the best performance in discriminating PD from neurological controls (sensitivity 82%; specificity 71%, area under the receiver operating characteristic curve = 0.87). These results demonstrate the possibility of detecting lysosomal dysfunction in CSF and further support the need to combine different biomarkers for improving the diagnostic accuracy of PD. © 2014 International Parkinson and Movement Disorder Society